2008
DOI: 10.2176/nmc.48.397
|View full text |Cite
|
Sign up to set email alerts
|

De Novo Formation of Cavernoma After Radiosurgery for Adult Cerebral Arteriovenous Malformation -Case Report-

Abstract: A 47-year-old male underwent stereotactic radiosurgery (25 Gy) for a cerebral arteriovenous malformation located in the right caudate nucleus, using a linear accelerator. Complete obliteration of nidus was confirmed 20 months after radiosurgery. However, a hypointense mass on T 2 -weighted magnetic resonance imaging developed in the area adjacent to the nidus after approximately 80 months. The mass gradually increased in size and induced severe perifocal edema over 2 years. The mass was successfully excised. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(24 citation statements)
references
References 22 publications
0
22
2
Order By: Relevance
“…Cavernous malformation development can occur after either conventional radiation 16 or stereotactic radiosurgery, 15,17 though all patients with radiation-induced cerebral CMs in this study had undergone conventional fractionated radiation. A prior systematic review of 76 patients with radiation-induced CMs showed a mean patient age of 11.7 years with a latency of 8.9 years after radiation until CM detection, 16 quite consistent with results seen in our study.…”
Section: Discussionmentioning
confidence: 81%
“…Cavernous malformation development can occur after either conventional radiation 16 or stereotactic radiosurgery, 15,17 though all patients with radiation-induced cerebral CMs in this study had undergone conventional fractionated radiation. A prior systematic review of 76 patients with radiation-induced CMs showed a mean patient age of 11.7 years with a latency of 8.9 years after radiation until CM detection, 16 quite consistent with results seen in our study.…”
Section: Discussionmentioning
confidence: 81%
“…We interpret 'expanding hematoma' to represent granulation tis- sue at the site of the obliterated AVM with hemorrhage [10,16] . Histological examination of expanding hematoma and cavernous angioma has been reported [10,11] . However, in our series, no cavernous angioma-like lesion was found.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10] The clinical features included: Adult onset except on patient younger than 20 years, male gender, high frequency of headache and seizure, high frequency of frontal or parietal lobe location, and presence of peri-lesional edema. Our patient had a past history of acute lymphoblastic leukemia, which can cause intracranial hemorrhage.…”
mentioning
confidence: 99%